Application of Guided Inquiry Learning Strategy on Thematic Learning of Science Material at Madrasah Ibtidaiyah - Rahayu, Ita Dwi; Prayogo, Muhammad Suwignyo (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to analyze the planning, implementation, and evaluation of the implementation of the Guided Inquiry learning strategy in thematic learning with the theme of Natural Sciences (IPA) at MI Miftahul Ulum III Sumbersari Gumukmas, Jember. The method used is a qualitative approach with the type of field research. Data collection was carried out through observation, interviews, and documentation. Data analysis refers to the interactive model of Miles, Huberman, and Saldana which consists of three stages: data condensation, data presentation, and drawing conclusions. Data validity is obtained through triangulation of techniques, sources, and time. The results of the study indicate that the implementation of the Guided Inquiry learning model in the classroom consists of several stages, namely: (a) Initial Activities, (b) Core Activities, (c) Final Activities, and (d) Learning Evaluation. The implementation of this strategy has proven effective in increasing students' interest in learning, especially in materials about invertebrates, changes in the state of objects, and conductors. The conclusion of this study is that the implementation of the Guided Inquiry strategy has a positive impact on students' interest in learning science in madrasah Ibtidaiyah.